Edible Bird's Nest Prevents Menopause-Related Memory and Cognitive Decline in Rats via Increased Hippocampal Sirtuin-1 Expression. (20th September 2017) - Hou, Zhiping; He, Peiyuan; Imam, Mustapha Umar; Qi, Jiemen; Tang, Shiying; Song, Chengjun; Ismail, Maznah
Abstract : Menopause causes cognitive and memory dysfunction due to impaired neuronal plasticity in the hippocampus. Sirtuin-1 (SIRT1) downregulation in the hippocampus is implicated in the underlying molecular mechanism. Edible bird's nest (EBN) is traditionally used to improve general wellbeing, and in this study, we evaluated its effects on SIRT1 expression in the hippocampus and implications on ovariectomy-induced memory and cognitive decline in rats. Ovariectomized female Sprague-Dawley rats were fed with normal pellet alone or normal pellet + EBN (6, 3, or 1.5%), compared with estrogen therapy (0.2 mg/kg/day). After 12 weeks of intervention, Morris water maze (four-day trial and one probe trial) was conducted, and serum estrogen levels, toxicity markers (alanine transaminase, alkaline phosphatase, urea, and creatinine), and hippocampal SIRT1 immunohistochemistry were estimated after sacrifice. The results indicated that EBN and estrogen enhanced spatial learning and memory and increased serum estrogen and hippocampal SIRT1 expression. In addition, the EBN groups did not show as much toxicity to the liver as the estrogen group. The data suggested that EBN treatment for 12 weeks could improve cognition and memory in ovariectomized female rats and may be an effective alternative to estrogen therapy for menopause-induced aging-related memory loss.